2014
DOI: 10.1037/hea0000069
|View full text |Cite
|
Sign up to set email alerts
|

Biased attentional processing of food cues and modification in obese individuals.

Abstract: Objective: This paper reports two experiments designed to investigate and modify biased attentional processing of food cues in obesity. Experiment 1: Experiment 1 used a dot probe task to show a food-related attentional bias in 58 obese women, relative to a comparison sample of normal weight controls. Experiment 2: Experiment 2 examined whether this bias can be modified. Using a modified dot probe task, 96 obese women were trained to attend to, or to avoid, food pictures. Attentional bias for food increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 53 publications
6
91
1
1
Order By: Relevance
“…The automatic basis of evaluative learning has been questioned [11], and some studies have found training effects in evaluative conditioning, and also cognitive bias modification only among individuals who are aware of the experimental contingencies (e.g., [1,16,59]). However, many other studies have shown that training effects in evaluative conditioning and cognitive bias modification are unaffected by contingency awareness (e.g., [5,[17][18][19]25,45,46]). Nevertheless, it is possible that awareness of the contingent appearance of food with either positive or negative stimuli in the current study may have influenced subsequent temptation and consumption.…”
Section: Discussionmentioning
confidence: 97%
“…The automatic basis of evaluative learning has been questioned [11], and some studies have found training effects in evaluative conditioning, and also cognitive bias modification only among individuals who are aware of the experimental contingencies (e.g., [1,16,59]). However, many other studies have shown that training effects in evaluative conditioning and cognitive bias modification are unaffected by contingency awareness (e.g., [5,[17][18][19]25,45,46]). Nevertheless, it is possible that awareness of the contingent appearance of food with either positive or negative stimuli in the current study may have influenced subsequent temptation and consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Each picture pair was individually matched on characteristics such as quality, brightness, and size, as well as ratings of pleasure and arousal. These ratings were obtained from a previous pilot study, in which 21 women aged 17-45 years (M = 23.67, SD = 8.28) rated 590 food and animal pictures on 9-point pleasure and arousal scales (Kemps, Tiggemann, & Hollitt, 2014). The same stimulus set was used for all three computer tasks.…”
Section: Methodsmentioning
confidence: 99%
“…In the study with obese participants, AB for food increased in the attend group and decreased in the avoid group, and the effects generalized to an independent measure of attentional bias. 66 The two studies that investigated ABM for chocolate achieved the same positive outcome, as AB for chocolate cues increased in the attend group and decreased in the avoid group, and these training effects generalized to novel, previously unseen chocolate pictures. Moreover, attentional retraining affected chocolate consumption and craving, and participants in the avoid group ate less chocolate in a so-called taste test than did those in the attend group.…”
Section: Eating Behaviormentioning
confidence: 86%
“…Six studies were identified, [62][63][64][65][66][67] and their tasks did not vary substantially, as they all a SOA of 500 ms and 12-20 pairs of food as a stimulus, although five used pictures and one used words. The three studies that compared attend and avoid groups 62,65,66 found AB changes and a significant impact of training. In the study with obese participants, AB for food increased in the attend group and decreased in the avoid group, and the effects generalized to an independent measure of attentional bias.…”
Section: Eating Behaviormentioning
confidence: 99%
See 1 more Smart Citation